Challenges and Opportunities in Green Financing within Nepal's Financial Sector - Chaudhary, Newal (Tribhuvan University Law Journal, 2025)
Green finance and sustainable investment are essential for promoting environmental sustainability in Nepal’s financial sector. While these efforts primarily aim to address environmental challenges, they also have the potential to indirectly support human rights by fostering ethical practices and improving working conditions within the sector, this article examines the critical role Nepal’s financial sector can play in advancing environmental sustainability and human rights through integrating green finance and sustainable investment. It provides an overview of Nepal’s financial landscape and the growth of sustainable finance globally and regionally. Strategies are proposed for financial institutions to build internal capacity, offer green financial products, improve disclosures and join relevant networks. Innovative instruments like green bonds, blended finance vehicles and sustainability-linked loans are explored. Opportunities for financing key sectors like renewable energy, eco-tourism and sustainable agriculture are highlighted. Importantly, the article calls for integrating human rights factors into green finance through mechanisms to link environmental and social risk, accountability and community participation. Multistakeholder collaboration is also examined as a way to mobilize green capital at scale. This article aims to explore the challenges and opportunities of integrating green finance within Nepal’s financial sector, with a focus on achieving a balance between profitability and ecological sustainability. It also examines the potential implications of green finance on human rights, particularly in promoting ethical practices and enhancing the social responsibility of financial institutions.